2020
DOI: 10.3390/ijerph17124573
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolar Treatment for Patients at Risk for Increased Intracranial Pressure: A Single-Center Cohort Study

Abstract: Treatment with osmoactive agents such as mannitol or hypertonic saline (HTS) solutions is widely used to manage or prevent the increase of intracranial pressure (ICP) in central nervous system (CNS) disorders. We sought to evaluate the variability and mean plasma concentrations of the water and electrolyte balance parameters in critically ill patients treated with osmotic therapy and their influence on mortality. This cohort study covered patients hospitalized in an intensive care unit (ICU) from January 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…It’s vital to understand that critical care pathways used to treat TBI may also influence distant organ dysfunction. For example, osmotic therapy may cause serious abnormalities in water-electrolyte balance [ 175 ], which in turn would be detrimental to the kidneys and the gut. Acute respiratory failure promotes organ ischaemia and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It’s vital to understand that critical care pathways used to treat TBI may also influence distant organ dysfunction. For example, osmotic therapy may cause serious abnormalities in water-electrolyte balance [ 175 ], which in turn would be detrimental to the kidneys and the gut. Acute respiratory failure promotes organ ischaemia and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…There is a dose–response relationship between the use of mannitol and the incidence and severity of AKI, with a cut-off of the daily dose at 1.34 g/kg body weight [ 73 ]. Interestingly, the combined therapy of ICH with mannitol and HTS did not increase the risk of AKI more than HTS alone, however several authors suggested to use HTS, demonstrating its superiority over mannitol [ 13 , 14 , 16 , 18 , 74 ]. In conclusion, it can be postulated that an increase in plasma hyperosmolality per se, as well as the use of osmotically active medications, may impair renal function, and that maintaining adequate renal perfusion may reduce the risk of AKI.…”
Section: Plasma Hyperosmolality and The Kidneymentioning
confidence: 99%